Respiratory viral infections in the lower respiratory tract failure (Literature review) - I. V. Babachenko; E. A. Kozyrev; E. V. Sharipova; E. D. Orlova; N. S. Tian (Журнал инфектологии)
The sharp increase in viral pneumonia against the background of the pandemic of the new coronavirus infection SARS-CoV-2 requires more attention to the study of the role of viruses in damage to the lower respiratory tract, including their etiological significance in the development of community-acquired pneumonia. Modern possibilities of laboratory diagnostics make it possible not only to identify and study respiratory viruses, but also to help differentiate active viral infections as a cause of lower respiratory tract disease from virus carriers. The review describes the epidemiological and clinical features of the most relevant or less studied pneumotropic viral infections in children (respiratory syncytial, adenovirus, bocavirus, metapneumovirus), including their role in the etiology of pneumonia in children. Understanding the viral etiology of pneumonia in children will reduce the antibacterial load, which will help to reduce the side effects of chemotherapy and slow the emergence of antimicrobialresistant bacterial strains.